Implementation Plan in Response to Board-Endorsed Recommendations Arising from the IEO Report on the Evaluation of the IMF Exchange Rate Policy Advice, 1999-2005. (Policy Papers; Policy Paper, 2007)
This paper presents an implementation plan that responds to the Board endorsed recommendations in the IEO Report on the Evaluation of the IMF's Exchange Rate Policy Advice, 1999-2005 ("the IEO Report"). The IEO recommendations and the views of the Executive Board are summarized in Section II, followed by descriptions of implementation plans (Section III) and the projected resource cost associated with the implementation plan (Section IV).